2021
DOI: 10.2352/j.imagingsci.technol.2021.65.6.060404
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Aware Halftoning Using the Iterative Method Controlling the Dot Placement

Abstract: Many image reproduction devices, such as printers, are limited to only a few numbers of printing inks. Halftoning, which is the process to convert a continuous-tone image into a binary one, is, therefore, an essential part of printing. An iterative halftoning method, called Iterative Halftoning Method Controlling the Dot Placement (IMCDP), which has already been studied by research scholars, generally results in halftones of good quality. In this paper, we propose a structure-based alternative to this algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…In our previous work, we used the local orientation of pixels to develop a structure-aware halftoning method based on IMCDP [21]. It has been shown that the structure-aware version of the IMCDP reproduces sharper halftones and better preserves the tone and structure similarity of the input image.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we used the local orientation of pixels to develop a structure-aware halftoning method based on IMCDP [21]. It has been shown that the structure-aware version of the IMCDP reproduces sharper halftones and better preserves the tone and structure similarity of the input image.…”
Section: Methodsmentioning
confidence: 99%
“…Abedini et al used the local orientations of the original image to align the halftone structure with the dominant line in each neighborhood. Their proposed structure-aware halftoning reproduces sharper halftones, while better preserves tonal and structural similarities compared to its non-structure-aware version [21]. Not all the proposed structure-aware halftoning methods have been tested on color images.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations